Global Awakening How 20th Century Revivals Triggered a Christian Revolution - Shaw, Mark (Illinois IVP Academic, 2010)
Mark Shaw's thesis is that far-flung revivals are at the heart of the global resurgence of Christianity. We read the stories of Joseph Babalola and the Aladura Revival in Africa, of Kil Sun-Ju and the great Korean revival of 1907, of Paulo Borges Jr. and explosion of neo-Pentecostalism in Brazil, and of V.S. Azariah and the mass conversions of the Dalit people in India. --from publisher description.
Keywords: Revivals -- Developing countries -- History -- 20th century. Developing countries -- Church history -- 20th century. Revivals. Developing countries